A trajetória da Oposição Bancária de São Paulo (1972 – 1979) - Munhoz, Regis Mendes [UNIFESP] (2019)
This work aims to investigate the formation of a group of bank workers in the city of São Paulo between 1972 and 1979, who were responsible for organizing the Opposition to the São Paulo Banking and Finance Union at the beginning of the decade. the union election in which the group ascends to power. It will be guided by the idea of becoming, or of constituting themselves as a group, through class, generational, educational, religious, regional experiences and by identities that characterize banking workers. It also seeks to understand how it was possible that the previous direction of the union (1965 - 1979) was able to isolate itself and lose the union machine. Finally, the objective is to understand, between the shattering of the old direction and the construction of a vision, as the group that was formed managed to elect in 1979.